Are socioeconomic composition effects on student achievement less relevant after de-tracking reforms in Germany? - Marlen Holtmann; Camilla Rjosk; Oliver Lüdtke; Petra Stanat (Large-scale Assessments in Education)
Abstract Recent de-tracking reforms in some German federal states converted or merged the two lower track secondary school types into a comprehensive one, where students can achieve all school-leaving qualifications. The goals of the reforms were to facilitate desegregation of students from different socioeconomic backgrounds and to reduce educational disparities. We investigated whether socioeconomic composition (SEC) and SEC effects have, in fact, changed with the de-tracking reforms. Moreover, we examined whether a possible increase in students' educational expectations of achieving the general qualification for university entrance contributes to the intended reduction of SEC effects. We used data from two representative large-scale assessment studies carried out in 2009 and 2015 covering the period of reforms. The SEC changed in non-academic school types. SEC effects on students' reading achievement tended to decrease, but are still significant in the comprehensive schools. The level of students’ educational expectations did not mediate the SEC effects.